Contextual Teaching and Learning (CTL) Model to Improve Reading and Writing Literacy Skills of Elementary School Students - Nicolas David Azizi; Ahmad Wahyulil Albab; Musrikah; Chusnul Chotimah (Social Journal of Studies in Education, 2026)
The low literacy skills of elementary school students remain a fundamental problem in learning. One effort that can be made to overcome this problem is to apply the Contextual Teaching and Learning (CTL) model. This study aims to: (1) describe the application of the CTL learning model in improving the reading and writing literacy skills of elementary school students, and (2) identify the supporting and inhibiting factors in the application of the CTL learning model. This study uses a qualitative approach with a literature study method. Data were obtained through the collection and analysis of various relevant literature sources, such as books, journal articles, previous research results, and other supporting documents related to CTL learning and reading and writing literacy in elementary schools. The results of this study indicate that CTL learning can improve students' reading and writing literacy skills through the relevance of learning materials to real-life contexts, meaningful learning activities, and active student involvement in the learning process. The supporting factors for the implementation of CTL are teacher readiness, availability of learning resources, and a conducive learning environment, while the inhibiting factors are time constraints, low teacher understanding of the CTL learning concept, and a lack of supporting facilities. Thus, the CTL learning model has the potential to be an effective alternative in improving the reading and writing literacy skills of elementary school students.